A study on the factors that influence job satisfaction among employees in accounting firm at Senawang Commercial Park / Muhammad Danial Firdaus Zamri - Zamri, Muhammad Danial Firdaus (Faculty of Business and Management, 2015)
In order to gain competitive advantage that enable the organization different from their competitor, the organization must also have their own talented and valued employee that will bring benefits to the company. The organization must recruit the talented employees in order to achieve the competitive advantage. However, the talented employees are not exactly loves their job or task given. As for accounting firm at Senawang Commercial Park, the researcher attracted to identify what are the determinants that make the employees satisfied with their job in that organization. Even though the organization is a medium organization, but the employees are loyal to the organization. The first research objective is to investigate the factors that contribute to job satisfaction among employees in accounting firm at Senawang Commercial Park. Second objectives are to ascertain the most factors that influence job satisfaction among employees in accounting firm at Senawang Commercial Park. The total respondents are 100 respondents which are the population of respondent is the similar number with sampling. The data were collected through distribution of questionnaire survey and interpreted into readable and informative data through Reliability Analysis, Descriptive Analysis and Pearson’s Correlation. The findings supported all the objectives which mean there is a significant relationship between all three independent variables which are working condition, leadership and pay/salary with the dependent variable, job satisfaction gaining in accounting firm at Senawang Commercial Park. In addition, leadership is the most influence factor to job satisfaction among employee.